A New Tool for Separating the Magnetic Mineralogy of Complex Mineral Assemblages from Low Temperature Magnetic Behavior - Lagroix, France; Guyodo, Yohan (Frontiers in Earth Science, 2017)
One timeless challenge in rock magnetic studies, inclusive of paleomagnetism and environmental magnetism, is decomposing a sample’s bulk magnetic behavior into its individual magnetic mineral components. We present a method permitting to decompose the magnetic behavior of a bulk sample experimentally and at low temperature avoiding any ambiguities in data interpretation due to heating-induced alteration. A single instrument is used to measure the temperature dependence of remanent magnetizations and to apply an isothermal demagnetization step at any temperature between 2 and 400 K. The experimental method is validated on synthetic mixtures of magnetite, hematite, goethite, as well as on natural loess samples where the contributions of magnetite, goethite, hematite and maghemite are successfully isolated. The experimental protocol can be adapted to target other iron bearing minerals relevant to the rock or sediment under study. One limitation rests on the fact that the method is based on remanent magnetizations. Consequently, a quantitative decomposition of absolute concentration of individual components remains unachievable without assumptions. Nonetheless, semi-quantitative magnetic mineral concentrations were determined on synthetic and natural loess/paleosol samples in order to validate and test the method as a semi-quantitative tool in environmental magnetism studies.